Factors Influencing Nurses’ Adherence to Standard Operational Procedures For Preventing Patient Falls - Rohmah, Lailatu; Prayoga, Diansanto (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Fall risk is one of the most frequently occurring patient safety incidents in hospitals and has become a global concern in efforts to improve the quality of healthcare services. This study aims to identify and analyze the factors that influence nurses’ compliance with standard operational procedures for fall prevention in hospital settings. The study employed a literature review approach by examining articles from reputable online databases. Three relevant articles were analyzed, revealing that factors such as attitude, knowledge, educational level, age, workload, length of work experience, availability of facilities, and the role of the head nurse are significantly associated with nurses’ compliance with standard operational procedures. Nurses with positive attitudes and knowledge, higher educational backgrounds, and supportive work environments tend to demonstrate higher adherence to fall prevention SPO. Nurses’ compliance with fall prevention standard operational procedures is influenced by multiple factors. Therefore, hospitals need to implement comprehensive interventions to enhance adherence and patient safety.